Coupling of protein localization and cell movements by a dynamically localized response regulator in Myxococcus xanthus - Leonardy, Simone (Nature Publishing Group, 2007)
Myxococcus xanthus cells harbor two motility machineries, type IV pili (Tfp) and the A-engine. During reversals, the two machineries switch polarity synchronously. We present a mechanism that synchronizes this polarity switching. We identify the required for motility response regulator (RomR) as essential for A-motility. RomR localizes in a bipolar, asymmetric pattern with a large cluster at the lagging cell pole. The large RomR cluster relocates to the new lagging pole in parallel with cell reversals. Dynamic RomR localization is essential for cell reversals, suggesting that RomR relocalization induces the polarity switching of the A-engine. The analysis of RomR mutants shows that the output domain targets RomR to the poles and the receiver domain is essential for dynamic localization. The small GTPase MglA establishes correct RomR polarity, and the Frz two-component system regulates dynamic RomR localization. FrzS localizes with Tfp at the leading pole and relocates in an Frz-dependent manner to the opposite pole during reversals; FrzS and RomR localize and oscillate independently. The Frz system synchronizes these oscillations and thus the synchronous polarity switching of the motility machineries.